PERANCANGAN USER EXPERIENCE APLIKASI PEMETAAN PEDAGANG KAKI LIMA DI KOTA MALANG - Muhammad Syukran Ni’matullah; Lutfi Fanani; Retno Indah Rokhmawati (Universitas Palangka Raya, 2022)
When starting to sell, there are several factors that must be considered before starting to trade, one of which is choosing a strategic location. However, choosing a strategic location is not easy because they have to consider several things and need to conduct surveys in various places, which certainly takes a long time. In addition, with the covid pandemic and the policy for the Implementation of Community Activity Restrictions (PPKM), the public cannot conduct direct surveys. In designing the Street Vendor Mapping Application in the city of Malang using the human-centred Design method because in designing this application, an approach involves the user of the application. At the testing stage, usability testing was carried out on 8 participants with the results getting the effectiveness aspect value of 91.96%, the efficiency aspect using the Time-Based Efficiency calculation of 0.091 goals/sec, and the satisfaction aspect getting a score of 80.94, which is level A, ranking Excellent, with acceptable category. Furthermore, User Experience testing was also carried out on 20 participants using the User Experience Questionnaire (UEQ) measurement with the results of the attractiveness aspect of 2.24, the perspicuity aspect of 2.16, the efficiency aspect of 2.39, the dependability aspect of 2.10, the stimulation aspect of 2.05, and the novelty aspect of 1.73.